Use of carbon-13 as a population marker for Anopheles arabiensis in a sterile insect technique (SIT) context - Knols Bart GJ; Mayr Leo; Hood-Nowotny Rebecca (Malaria Journal, 2006)
Abstract Background Monitoring of sterile to wild insect ratios in field populations can be useful to follow the progress in genetic control programmes such as the Sterile Insect Technique (SIT). Of the numerous methods for marking insects most are not suitable for use in mass rearing and mass release. Suitable ones include dye marking, genetic marking and chemical marking. Methods The feasibility of using the stable isotope of carbon, 13C, as a potential chemical marker for Anopheles arabiensis was evaluated in the laboratory. Labeled-13C glucose was incorporated into the larval diet in a powder or liquid form. The contribution of adult sugar feeding to the total mosquito carbon pool and the metabolically active carbon pool was determined by tracing the decline of the enrichment of the adult male mosquito as it switched from a labeled larval diet to an unlabeled adult diet. This decline in the adult was monitored by destructive sampling of the whole mosquito and analyzed using isotope ratio mass spectrometry. Results A two-pool model was used to describe the decline of the 13C-enrichment of adult mosquitoes. The proportion of the total adult carbon pool derived from the adult sugar diet over the life span of mosquitoes was determined and the ratio of structural carbon, with a low turnover rate to metabolically active non-structural carbon was assessed. The uptake and turnover of sugar in the metabolically active fraction suggests that after 3 days >70% of the active fraction carbon is derived from sugar feeding (increasing to >90% by day 7), indicating the high resource demand of male mosquitoes. Conclusion It was possible to "fix" the isotopic label in adult An. arabiensis and to detect the label at an appropriate concentration up to 21 days post-emergence. The optimum labeling treatment would cost around 250 US$ per million mosquitoes. Stable isotope marking may thus aid research on the fate of released insects besides other population-based ecological studies.